Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1086/346076
|View full text |Cite
|
Sign up to set email alerts
|

The BIMA Survey of Nearby Galaxies (BIMA SONG). II. The CO Data

Abstract: The BIMA Survey of Nearby Galaxies is a systematic imaging study of the 3 mm CO J ¼ 1 0 molecular emission within the centers and disks of 44 nearby spiral galaxies. The typical spatial resolution of the survey is 6 00 or 360 pc at the average distance (12 Mpc) of the sample. The velocity resolution of the CO observations is 4 km s À1 , though most maps are smoothed to 10 km s À1 resolution. For 33 galaxies, multifield observations ensured that a region e190 00 (hDi ¼ 10 kpc) in diameter was imaged. For the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
414
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(446 citation statements)
references
References 59 publications
30
414
2
Order By: Relevance
“…Comparison between the integrated SCO fluxes determined by Kuno et al (2007) and those determined by Helfer et al (2003; red filled dots), Chung et al (2009a; blue filled triangles), our own observations of the two galaxies NGC 4548 and NGC 4579 with the IRAM radiotelescope (green filled squares) and the extrapolated fluxes of the FCRAO survey (Young et al 1995; cyan empty circles) on logarithmic scale for all galaxies in common (left) and on linear scale for those objects with SCO in the range 100-5000 Jy km s −1 sampled by the HRS (right). The linear best fit to the data, determined assuming the Kuno et al (2007) data as independent variable in the range 100-5000 Jy km s −1 , are shown by the red dotted line (Helfer et al 2003), the blue long dashed line (Chung et al 2009a) and the cyan solid line (Young et al 1995).…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparison between the integrated SCO fluxes determined by Kuno et al (2007) and those determined by Helfer et al (2003; red filled dots), Chung et al (2009a; blue filled triangles), our own observations of the two galaxies NGC 4548 and NGC 4579 with the IRAM radiotelescope (green filled squares) and the extrapolated fluxes of the FCRAO survey (Young et al 1995; cyan empty circles) on logarithmic scale for all galaxies in common (left) and on linear scale for those objects with SCO in the range 100-5000 Jy km s −1 sampled by the HRS (right). The linear best fit to the data, determined assuming the Kuno et al (2007) data as independent variable in the range 100-5000 Jy km s −1 , are shown by the red dotted line (Helfer et al 2003), the blue long dashed line (Chung et al 2009a) and the cyan solid line (Young et al 1995).…”
Section: Figmentioning
confidence: 92%
“…The linear best fit to the data, determined assuming the Kuno et al (2007) data as independent variable in the range 100-5000 Jy km s −1 , are shown by the red dotted line (Helfer et al 2003), the blue long dashed line (Chung et al 2009a) and the cyan solid line (Young et al 1995). The short dashed black line shows the 1:1 relationships.…”
Section: Figmentioning
confidence: 95%
“…Utilizing data from the THINGS, HERACLES, and BIMA SONG surveys Leroy et al, 2009;Helfer et al, 2003), Bigiel et al (2008) investigated the resolved star formation law in nearby galaxies. These authors found that the SFR is principally correlated with H 2 gas (as traced by CO (J=2-1) in this case), and unassociated with HI in nearby galaxies.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 99%
“…1, the Σco and σco profiles presented here are derived up to R = 3 kpc, but we exclude the central R = 350 pc because such a region is highly disturbed by a massive AGN-driven outflow (García-Burillo et al 2014). The surface density of molecular gas is converted to physical units by adopting the standard CO-to-H2 conversion factor, Xco = 2 × 10 20 cm −2 (K km s −1 ) −1 (Bolatto et al 2013), consistent with Helfer et al (2003). We also correct for the contribution of helium multiplying by a factor of 1.36.…”
Section: Molecular Gasmentioning
confidence: 99%